(3COH GdChUjGA aj GdaQhYs - (3Ydj Hf CMeO Hf eMeO GdLeGdj GdHcQj , YdGA GdOjf,J (B932 (3g` s ((3EHQGgje Hf fhM Hf Ydi Gdcahi s)
(3ChdgG (B:s
(3bGd CHh GdYHGS SeYJ GdTjN CHG GdeMSf Hf SQGbI jbhd GdeQCI EPG Oe GdMjV JYdb Hg CMcGe s
(3BNQgG (B:s
(3dG jcQg ai LejY GdCjGe EdG ai NeSI CjGe hGddg JYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B25 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B742s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B45s
Keywords: (3Gdabg GdMfajs